The Application of iPSCs in Tumour Immunotherapy - Peinan Chen; Jian Gao; Jianing Feng; Hongfei Tao; Yongkui Yu; Yijing Li; Jinlong Liu; Shuangshuang Lu; Wei Wang (Expert Reviews in Molecular Medicine)
Abstract Background Tumour immunotherapy holds great promise as a treatment for cancer, which ranks as the second highest cause of mortality worldwide. This therapeutic approach can be broadly categorized into two main types: active immunotherapy and passive or adoptive immunotherapy. Active immunotherapy, such as cancer vaccines, stimulates the patients’ immune system to target tumour cells. On the other hand, adoptive immunotherapy involves supplying in vitro activated immune cells, such as T cells, natural killer cells and macrophages, to the patient to combat the tumour. Induced pluripotent stem cells are extensively utilized in both active and adoptive tumour immunotherapy due to their pluripotency and ease of gene editing. They can be differentiated into various types of immune cells for direct cancer treatment and can also function as tumour vaccines to elicit an immune response against the tumour. Importantly, iPSCs can be leveraged to develop off-the-shelf allogenic immunotherapy products.